Impact of Product Packaging on Consumer Buying Behaviour - Banerjee, Sudip (Journal of Advanced Research in Humanities and Social Sciences, 2024)
Introduction: Consumer is the ultimate user of a product, in case of 1st time buying decisions on store or shop may influence with product packaging, even in case of subsequent buying decisions of the same product irrespective of the quantity or other factors like price, product packaging role cannot be ignored. So, this research paper discusses consumer buying behaviour towards product packaging emphasizing how various packaging elements such as package design, package colour, package material, and package sustainability affect consumer perceptions and purchasing decisions. The relationship between the independent and dependent variables was also determined by this study. Research Objectives: The main objective of this study is to understand the product packaging effects on consumer buying behaviour. Research Method: Structure questionnaire 105 responses were taken for the study. Data analysis with the regression, coefficient, and Kruskal-Wallis Test. Results: From the study it has been revealed that eco-friendliness and the colour of the package significantly affect the buying behaviour of the customers. Other factors like package material, attractiveness, quality packaging, and hygiene packaging have no effect on the buying decisions of customers. Conclusion: The analysis showed that packaging has been shown to be the important component which impacts consumer buying behaviour. Colour of the packet which attract customers similarly these days’ people have shown concerned on environment which is good for society and people prefer eco-friendly packaging of products.